2016
DOI: 10.1007/s13365-015-0420-5
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system-specific consequences of simian immunodeficiency virus Gag escape from major histocompatibility complex class I-mediated control

Abstract: In the fourth decade of the HIV epidemic, the relationship between host immunity and HIV central nervous system (CNS) disease remains incompletely understood. Using a simian immunodeficiency virus (SIV)/macaque model, we examined CNS outcomes in pigtailed macaques expressing the MHC class I allele Mane-A1*084:01 which confers resistance to SIV-induced CNS disease and induces the prototypic viral escape mutation Gag K165R. Insertion of gag K165R into the neurovirulent clone SIV/17E-Fr reduced viral replication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Given that a single-epitope vaccine is not likely to prevent SIV or HIV infection because of potential development of escape mutations, studies in which macaques are vaccinated with multiple SIV Gag epitopes (as well as epitopes beyond Gag) are needed. In addition, our data support development of a therapeutic vaccine approach to control CNS reservoirs given that stimulating Mane-A1*084 -mediated CTL responses by virus-like particle (VLP) KP9 vaccination prior to SIV infection had a CNS-specific protective effect with lower CSF viral loads (34). Ongoing efforts aim to identify whether therapeutic vaccination protocols employing a similar strategy to stimulate CNS-specific MHC class I mediated responses may be pivotal in HIV cure efforts, especially for targeting the CNS compartment.…”
Section: Role Of Mhc Class I Alleles In Siv Cns Diseasementioning
confidence: 53%
“…Given that a single-epitope vaccine is not likely to prevent SIV or HIV infection because of potential development of escape mutations, studies in which macaques are vaccinated with multiple SIV Gag epitopes (as well as epitopes beyond Gag) are needed. In addition, our data support development of a therapeutic vaccine approach to control CNS reservoirs given that stimulating Mane-A1*084 -mediated CTL responses by virus-like particle (VLP) KP9 vaccination prior to SIV infection had a CNS-specific protective effect with lower CSF viral loads (34). Ongoing efforts aim to identify whether therapeutic vaccination protocols employing a similar strategy to stimulate CNS-specific MHC class I mediated responses may be pivotal in HIV cure efforts, especially for targeting the CNS compartment.…”
Section: Role Of Mhc Class I Alleles In Siv Cns Diseasementioning
confidence: 53%
“…They define novel determinants of SIV macrophage tropism and neutralization sensitivity in two N-linked glycosylation sites in the V2 and C5 regions (N173 and N481), suggesting that macrophage-tropic SIV capable of establishing viral reservoirs in the brain can be present in blood very early in infection [ 48 ]. Similarly, data obtained in SIV-infected pigtailed macaques indicate that viral variants detected early in infection in CSF reemerge after ART interruption, implying that these variants are archived in latent proviral DNA, and that the CNS may serve as a viral reservoir [ 49 , 50 ]. Since brain macrophages harbor replication-competent virus capable of re-establishing infection upon treatment interruption [ 50 ] it is possible that these cells are responsible for production of compartmentalized viral variants found in this site.…”
Section: Viral Sequence Evolution and Host Geneticsmentioning
confidence: 99%
“…Moreover, Mane-A1*084:01-positive macaques, first vaccinated with a virus-like particle-based Gag KP9 peptide to induce CTL responses on Gag KP9 and then challenged with wild type SIV/17E-Fr, had lower viral load in CSF compared to unvaccinated controls, but showed no difference in plasma viral loads. This result suggests that Mane-A1*084 -associated CTL control is crucial to control viral replication in the CNS [ 49 ].…”
Section: Viral Sequence Evolution and Host Geneticsmentioning
confidence: 99%
“…As such, a number of behavioral and biological abnormalities are currently being investigated in macaques as potential markers of brain dysfunction to be used for studies of the CNS reservoirs in SIV-infected ART-treated RM. Recently, Beck et al showed a difference in infection efficiency of the virus infecting the CNS compared to the periphery (80). These authors characterized the viral fitness of both wild type SIV and the specific CTL escape mutant (K165) to show that the perivascular CTL response exerts selective pressure on wild type SIV in the CNS but not in the periphery, suggesting that the virus causing CNS infection may be different from its peripheral counterpart.…”
Section: Siv Cure Strategiesmentioning
confidence: 99%